2015
DOI: 10.1021/ef5025559
|View full text |Cite
|
Sign up to set email alerts
|

Microfracture and Surfactant Impact on Linear Cocurrent Brine Imbibition in Gas-Saturated Shale

Abstract: During and after hydraulic fracturing, fluid–shale interaction has a prominent impact on liquid retention and thus on gas phase permeability and gas productivity. By providing a low surface tension or wettability alteration, surfactants are widely used to decrease liquid retention after fracturing. To evaluate the liquid intake of a rock sample, an imbibition experiment is commonly used, especially when it is treated by a surfactant. However, conventional imbibition experiments with gas shale could not quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…Recently, many publications have reported that micro-fractures, which can take up a significant amount of water, are created due to swelling of clays by absorbing water molecules (Makhanov et al 2014;Roshan et al 2015;Sun et al 2015;Zhou et al 2016;. As expected, imbibition of oil should create fewer micro-fractures compared to imbibition of water, and this was demonstrated by Makhanov (2013) as shown in Figure 2.…”
Section: Fractures Micro-fractures and Matrixmentioning
confidence: 61%
“…Recently, many publications have reported that micro-fractures, which can take up a significant amount of water, are created due to swelling of clays by absorbing water molecules (Makhanov et al 2014;Roshan et al 2015;Sun et al 2015;Zhou et al 2016;. As expected, imbibition of oil should create fewer micro-fractures compared to imbibition of water, and this was demonstrated by Makhanov (2013) as shown in Figure 2.…”
Section: Fractures Micro-fractures and Matrixmentioning
confidence: 61%
“…The cumulative imbibed volume increases with time. However, the rate of water intake obviously slows down with increasing time, and the rate approximately reaches zero, which represents the equilibrium condition (Sun et al 2015). However, some curves may have ''upward tails,'' which demonstrate an obvious diffusion effect and may be related to the complex pore structure in these rock samples, as shown in Fig.…”
Section: Imbibition Curve Characteristicsmentioning
confidence: 89%
“…The ultimate fate of the lost hydraulic fracturing treatment water (*70% of total injected volume) and the role that these fluids may have in altering reservoir gas production remain an open question (Cheng, 2012;Jackson et al, 2014). Previous studies and industry experience suggest that liquid imbibed into tight rocks is easily trapped near the fracture face and is not usually drained during production due to the strong capillary forces (Bennion et al, 1996;Dehghanpour et al, 2013;Sun et al, 2015). Increased liquid trapping and water saturation in the rock near the fracture would thus reduce gas relative permeability and impair reservoir gas productivity (Bennion et al, 1994).…”
Section: Introductionmentioning
confidence: 99%